Can we improve a Soviet city: Strategic Environmental Assessment of the Master Plan for Narva in Estonia - Rein Ahas; Evelyn Koduvere; Ülar Mark (European Regional Science Association (ERSA), 2001)
The objective of our planning project was to study the possibilities how to support industrial development of Narva (Estonia) with the improving of urban infrastructure and life quality in city. We studied the Narva city master plan with the aim of finding new strategies for using the ruins of Soviet city and a industry for developing an industrial network. The reality of today's Narva economy is that there are some existing industries which use old technology and some new enterprises with plenty of qualified workers in the region. There is privatised thermal power plants supplying all Estonia with energy and Narva is a huge transit channel between Russia and the Tallinn harbour. The Russian border is in the middle of the city and Saint Petersburg with a population of 5 million is only 130 km away. This potential is still attractive for investment and industrial development. Development problems of Narva are connected with old infrastructure and housing. City was destroyed during second world war, today, 95% of housing consist typical soviet block houses which will be amortised during next 20 years. Infrastructure network is divided with Russia and it is amortised. There is no attractive apartments or districts in Narva for non-local specialists. Because of low housing quality, most of 300 managers live in other cities and they only visit working place. Our planning strategy was to create new urban environment for Narva. The transportation network, infrastructure and street lines were reorganised with aim to create new city centre and qualitative residential areas. The renovation and demolishing strategy was developed for soviet block houses.
Keywords: 330